A Living‐Dead Magnetic Layer at the Surface of Ferrimagnetic DyTiO3 Thin Films. Issue 29 (30th May 2018) - Aeschlimann, Raphaël; Preziosi, Daniele; Scheiderer, Philipp; Sing, Michael; Valencia, Sergio; Santamaria, Jacobo; Luo, Chen; Ryll, Hanjo; Radu, Florin; Claessen, Ralph; Piamonteze, Cinthia; Bibes, Manuel
Abstract: When ferromagnetic films become ultrathin, key properties such as the Curie temperature and the saturation magnetization are usually depressed. This effect is thoroughly investigated in magnetic oxides such as half‐metallic manganites, but much less in ferrimagnetic insulating perovskites such as rare‐earth titanates RTiO3, despite their appeal to design correlated 2D electron gases. Here, the magnetic properties of epitaxial DyTiO3 thin films are reported. While films thicker than about 50 nm show a bulk‐like response, at low thickness a surprising increase of the saturation magnetization is observed. This behavior is described using a classical model of a "dead layer" but assuming that this layer is actually "living, " that is, it responds to the magnetic field with a strong paramagnetic susceptibility. Through depth‐dependent X‐ray absorption and photoemission spectroscopy, it is shown that the "living‐dead layer" corresponds to surface regions where magnetic ( S = 1/2) Ti 3+ ions are replaced by nonmagnetic Ti 4+ ions. Hysteresis cycles at the Dy M 5 and Ti L 3 edges indicate that the surface Ti 4+ ions decouple the Dy 3+ ions, thus unleashing their strong paramagnetic response. Finally, it is shown how capping the DyTiO3 film can help increase the Ti 3+ content near the surface and thus recover a better ferrimagnetic behavior. Abstract : A peculiar magnetic "dead layer" is detected at the surface of thin films of DyTiO3, a ferrimagnetic Mott insulator. Depth‐dependent X‐ray spectroscopy indicates that this layer is associated with a deviation of the Ti valence from 3+ toward 4+ at the film surface, suppressing the magnetic coupling between Ti ions and unleashing a strong paramagnetic response from uncoupled Dy ions.